To Increase Mental Health Literacy and Human Rights Among New-Coming, Low-Educated Mothers With Experience of War: A Culturally, Tailor-Made Group Health Promotion Intervention With Participatory Methodology Addressing Indirectly the Children - Ekblad, Solvig (Frontiers in Psychiatry, 2020)
Due to the increasing numbers of newcomers with impacts of war, civil war and persecution, at high risk of trauma-related mental health problems, there is a need for increase the poor mental health literacy (MHL) and human rights among the new-comers, especially low-educated mothers with children. This book chapter will give a case study report of several years’ experience of tailor-made group health promotion intervention, describe an ongoing project in different parts of Sweden and in collaboration between academia, primary care, social welfare, police and a NGO. These interventions are recommended to focus on human rights, psychosocial and parenting support for war-affected parents, especially the low-educated mothers by using a five week’s group intervention a two hours/week including evaluation. Further, it is vital that these interventions towards the target group with limited exposure to Western concepts (eg, illness, anxiety, trauma), may bridge the gap between Western and traditional cultural understanding of pre- and postmigration stress. In conclusion, MHL may be a function of both the cultural origin of the target group’s background and their resettlement in a Western reception country. Implications are discussed.